Latanoprost Induced Iris Pigment Epithelial and Ciliary Body Cyst Formation in Hypermetropic Eyes - Abhijit Anand Mohite; Rangarajan V. Prabhu; Thomas Ressiniotis (Case Reports in Ophthalmological Medicine)
Purpose. Latanoprost has become one of the most widely prescribed topical antihypertensive medications in recent years. Yet there have been few reports of secondary iris pigment epithelial (IPE) and ciliary body (CB) cyst formation to date and none, to our knowledge, reported in eyes predisposed to primary angle closure. Methods. We report the first documented case of bilateral IPE and CB cysts in a hypermetropic patient with prior laser peripheral iridotomies (LPIs) as a rare, delayed side effect of topical Latanoprost treatment. The cysts subsided with discontinuation of Latanoprost, thereby demonstrating a causal relationship. We discuss the pathogenesis of such cysts and advocate using of serial ultrasound biomicroscopic (UBM) images to monitor them. Results and Conclusions. Latanoprost may cause iris pigment epithelial and ciliary body cysts that remain clinically undetected. In eyes predisposed to angle closure, such cysts may become clinically detectable and masquerade as iris tumours. Prior laser peripheral iridotomies in these eyes may delay or prevent the detection of these cysts. Ultrasound biomicroscopy (UBM) imaging is therefore a valuable tool in diagnosing and monitoring these cysts.